Azelaic Acid. Issue 3 (May 2017) - Bergman, Daniel; Luke, Janiene
Abstract : ABSTRACT: The purpose of this column is to highlight medications commonly used in the field of dermatology: how they work, how they are utilized, side effects, and available alternatives. This article discusses the mechanism of action, usage, adverse effects, and alternatives of the commonly used topical medication azelaic acid as a treatment for acne vulgaris, rosacea, and postinflammatory hyperpigmentation.